The Design of Low Thrust Engine Spacecraft for Near-earth Asteroid Exploration. (2017) - Khabibullin, Roman M.; Starinova, Olga L.; Fain, Maxim K.; Alipova, Bakhyt N.; Yudong, Hu
Abstract: This paper discusses the application of computer-assisted design systems to development of low thrust spacecraft intended to take an exploratory flight to potentially hazardous asteroids. The design model of the low thrust spacecraft that is created with computer-aided design systems is described. The mathematical motion model within the heliocentric system of coordinates for such type of spacecraft is considered and used for a motion simulation session. The simulation of flight to the potentially hazardous asteroid is performed with the aid of special complex software that is developed for the purpose of the work. The results of the paper consist of a detailed three-dimensional model of the low thrust spacecraft, heliocentric trajectory of the spacecraft, the values of flight duration and propellant consumption during exploratory flight.